PERANAN BUDAYA ORGANISASI, DIFERENSIASI DAN INOVASI TERHADAP SUSTAINABLE COMPETITIVE ADVANTAGE (SCA) (Studi Empiris Perum Pegadaian Syariah Se Malang Raya) - Leksono, Agung Budi; Sucipto, Agus (IQTISHODUNA, 2015)
The problem of this research is the development of pawning institution. It seems slowly developedand hardly to complete with other pawning institutions. Therefore, some factors causing this problem need tobe understood. Against this problem, the author feels necessary to examine some factors with important effecton Syariah pawning, such as differentiation, organizational culture, and innovation. Research type is explanatoryresearch, in which it explains the causal relationship between research variables through hypothesis testing.Population of research is manager with authority of strategic decision making in the syariah pawning institutionin Malang City. Sample is taken by census technique. Furthermore the data will be subjected to MultipleRegression Analysis. Result of research indicates that Differentiation, Organizational Culture, and Innovationinfluence sustainable competitive advantage. It may be concluded that higher level of Differentiation,Organizational Culture, and Innovation in the pawning institution can produce higher sustainable competitiveadvantage for pawning institutions in Malang.